Soil Functionality Undermined by Symbiotic Fungal Decline Following Forest Conversion - Xinjing Qu; Yangwenke Liao; Catherine W. Muthuri; Leigh Ann Winowiecki; Haiyun Zi; Yang Zhang; Xiaogang Li (Environmental Microbiology, 2026)
The conversion of native forests to other terrestrial ecosystems represents a profound form of land‐use change, threatening aboveground biodiversity and biomass. However, its impact on soil ecological functions remains uncertain, particularly the regulatory role of soil microbial communities. To address this, we evaluated soil functionality related to carbon, nitrogen and phosphorus cycling by measuring nine enzyme activities in soils from native forests, plantations and croplands in subtropical China. Our results demonstrated a significant decline in soil functionality following the conversion of native forests, with the most pronounced reductions observed in croplands. This decline in soil functionality was strongly associated with a decrease in fungal richness but was independent of bacterial alpha‐diversity. Specifically, the reduction in the abundance of symbiotic fungi, including key taxa such as Lactifluus and Tomentella , was identified as a primary driver of the functional impairment. Metagenomic analyses further confirmed that the loss of microbial functional genes was linked to the observed decline in soil functionality. Our findings underscore the critical role of key fungal taxa in maintaining soil processes and highlight the importance of their conservation and restoration to ensure ecosystem functionality in managed landscapes.